2011
DOI: 10.5104/jiepeng.4.31
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Thermal Scaling Analysis of Si MOSFETs with Device Length Typically Larger than 100nm

Abstract: Scaling consideration is applied to the coupling electro-thermal characteristics of Si MOSFETs with device length typically larger than 100 nm. The non-equilibrium nature of the electrons and the crystal lattice is considered. Both lumped and rigorous electro-thermal models are deployed to examine the device thermal trend with device scaling. The lumped model considers the self-heating of the device and the resulting electron and lattice temperature rise. The results show that the non-equilibrium nature of ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…The governing equations of electro-thermal analysis consist of the continuity equation, momentum conservation equation, and energy conservation equation [ 5 ]. The non-equilibrium nature of electrons and phonons becomes critical for devices with gate lengths typically shorter than 1 μm [ 6 ]. Non-equilibrium state between electron temperature and lattice temperature results that electron temperature becomes much higher than lattice temperature due to electro-thermal effect [ 5 – 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The governing equations of electro-thermal analysis consist of the continuity equation, momentum conservation equation, and energy conservation equation [ 5 ]. The non-equilibrium nature of electrons and phonons becomes critical for devices with gate lengths typically shorter than 1 μm [ 6 ]. Non-equilibrium state between electron temperature and lattice temperature results that electron temperature becomes much higher than lattice temperature due to electro-thermal effect [ 5 – 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hot-electron phenomena in semiconductor devices can be analyzed by using the continuity equation, momentum conservation equation, and energy conservation equation 9 . For transistors with the gate length less than micrometer, the non-equilibrium nature of electrons and phonons must be considered 10 . The electron energy (electron temperature) can be much higher than lattice energy (lattice temperature) in semiconductor devices 9 10 11 , while the energy difference between electrons and lattices is governed by the energy relaxation (ER) time 12 .…”
mentioning
confidence: 99%
“…For transistors with the gate length less than micrometer, the non-equilibrium nature of electrons and phonons must be considered 10 . The electron energy (electron temperature) can be much higher than lattice energy (lattice temperature) in semiconductor devices 9 10 11 , while the energy difference between electrons and lattices is governed by the energy relaxation (ER) time 12 . Experimental results showed that the ER time in a graphene device is about 1 ps, and the electron gas temperature varies from 400 K to 700 K when the lattice temperature is 300 K in single-wall carbon nano-tubes 13 .…”
mentioning
confidence: 99%